2004
DOI: 10.1142/s1088424604000350
|View full text |Cite
|
Sign up to set email alerts
|

Phenyl biliverdin isomers obtained by chemical oxidation of iron(III) complex of 5-phenyl protoporphyrin IX

Abstract: Oxidative cleavage of synthetic 5-phenyl protohemin IX in pyridine solution in the presence of ascorbic acid (coupled oxidation), followed by esterification of the products with boron trifluoride-methanol rendered mainly three isomeric biliverdins. These were identified by MS and 1D and 2D 1 H NMR as 15-phenyl biliverdin IXβ (1), 10-phenyl biliverdin IXγ (2) and 5-phenyl biliverdin IXδ (3) dimethyl esters. The fact that biliverdin IXα dimethyl ester derivative is not obtained indicates that oxidation fails to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The dimethyl esterified biliverdin isomers were prepared from the corresponding heme by coupled oxidation in the presence of pyridine, O 2 , and ascorbic acid according to published procedures (27,28 (29). Enzymes-Truncated hHO-1 lacking the 23 C-terminal residues was expressed and purified according to published procedures (23,30,31).…”
Section: Methodsmentioning
confidence: 99%
“…The dimethyl esterified biliverdin isomers were prepared from the corresponding heme by coupled oxidation in the presence of pyridine, O 2 , and ascorbic acid according to published procedures (27,28 (29). Enzymes-Truncated hHO-1 lacking the 23 C-terminal residues was expressed and purified according to published procedures (23,30,31).…”
Section: Methodsmentioning
confidence: 99%
“…Although meso-substituted porphyrins were employed as a substrate for the enzyme reactions, the substrate of the coupled oxidation has been limited to the iron complexes of meso-unsubstituted porphyrins such as protoporphyrin IX and octaethylporphyrin. Recently, Niemevz et al reported that meso -monophenylporphyrin underwent coupled oxidation where the meso-unsubstituted carbon was selectively oxidized …”
Section: Introductionmentioning
confidence: 99%